2021
DOI: 10.1080/09692290.2021.1935294
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization or flexibilization? The changing role of technology in the political economy of Japan

Abstract: We are increasingly surrounded by talk of digitalization. Yet, we remain unsure about what impact this digitalization will have upon socio-economic institutions, how the introduction of this digitalization will be contested, the likely role of the state in managing the adoption of digital technology, and the likely consequences for the broader political economy if and when it is introduced. This article examines the process of digitalization as it has unfolded in the service sector in Japan. Based on qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 37 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…Hence, if there is more knowledge about what can be done digitally, there is little sign that this will drive broader and beneficial usage of digitalization across the wider economy, or improve the competitive position of firms at large. Again, whilst optimistic accounts have suggested that digitalization may make firms more competitive, whilst improving the position of workers, more pessimistic accounts highlight how this has contributed to closer surveillance and task fragmentation (Shibata, 2021). The latter can be without improving productivity or adding value to the production process.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, if there is more knowledge about what can be done digitally, there is little sign that this will drive broader and beneficial usage of digitalization across the wider economy, or improve the competitive position of firms at large. Again, whilst optimistic accounts have suggested that digitalization may make firms more competitive, whilst improving the position of workers, more pessimistic accounts highlight how this has contributed to closer surveillance and task fragmentation (Shibata, 2021). The latter can be without improving productivity or adding value to the production process.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with the vaccination process in other countries indicated the expectation of a prompt vaccination process in Japan. The claims regarding problems with the reservation system and vaccine-related telephone scams showed the urgency of building a convenient and safe pipeline for vaccine distribution and reservation, presenting the challenge of both the flexibility of the medical care system [ 8 ] and the acceleration of the digitalization process [ 59 ] in Japan. Concerns about the Olympics were also caused by the slow progress of anti-epidemic measures and the vaccination process but also showed the need for risk evaluation by policy makers balancing public health and other factors [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shibata argues that digitalisation has gone hand in hand with a move towards a more profit-driven model of capitalism in Japan; where flexibilisation of the labour market and restructuring of many firms was seemingly facilitated by a move towards a Society 5.0 'workstyle' that has introduced tele-working and the integration of robots at work. Rather than somehow ease work as some 'technooptimists' predicted, these moves have not improved the wage labour nexus, but rather led to a depression of wages, unpaid overtime and worsening protections for workers (Shibata, 2021).…”
Section: Debates In Key Journalsmentioning
confidence: 99%
“…What has been largely missing in our discipline, however, is an explicit, critical discussion on technology, work, and the global political economy. We have already discussed the articles by Moore and Joyce (2020) and Shibata (2021) in RIPE. There is a further small number of researchers with a background in International Relations and Global Political Economy who in some cases have entered other disciplines, but who have nonetheless led on discussions about the emergence of the platform in corporate terms; digital tracking; and algorithmic operations; and warned about their significance and implications for Global Political Economy research, with some discussion of the implications for work and workers.…”
Section: Debates In Key Journalsmentioning
confidence: 99%